Numerical investigation of high viscous fluid flow between two porous plates using the shooting technique. (2015) - Hona, Jacques; Nyobe, Elisabeth Ngo; Pemha, Elkana
The horizontal channel consists of two parallel rigid plates. These plates are uniformly porous and fixed at different temperatures. The problem is modelled by means of the Navier-Stokes equations and the energy equation. The similarity technique leads to introduce the stream function in the governing equations. The investigation is then reduced to solve a non-linear two-point boundary-value problem with six boundary conditions by applying a numerical strategy based on the shooting method. The numerical results show that the temperature distribution presents a large area of inflection through the channel under certain values of control parameters. The maxima of thermal gradients are located at the walls due to suction. The high viscosity of the fluid is favourable to the existence of the reverse flow and is adverse to suction. For a given Reynolds number, the normal pressure gradient is very sensitive to the temperature difference between the walls.